Possible Nonneurological Health Benefits of Ketogenic Diet: Review of Scientific Reports over the Past Decade - Katarzyna Daria Gołąbek; Bożena Regulska-Ilow (Hindawi Limited, 2022)
The ketogenic diet (KD) has been used since the 1920s as a therapy for drug-resistant epilepsy. Due to the beneficial effects of this diet on the nervous system and the proposed multifaceted effects of ketones on health and disease, researchers have evaluated its use in other nonneurological conditions. The objective of this review was to analyze the most recent papers, which is why meta-analyses were used in which 75% of the studies were from 2012 to 2022. Authors also cited single studies from the last decade that lasted longer than 12 months to assess the long-term benefits of KD. Reports from the past decade have highlighted several significant areas regarding the impact of KD. One of these is the use of very low-calorie ketogenic diet (VLCKD) as an effective possibly safe and patient-motivating component of a long-term weight loss plan. Reports on the positive influence of KD on the health of obese individuals, and the possible resulting validity of its use, should be verified by patients' physical activity levels. A significant number of studies from the last decade evaluate the effect of KD on improving the health of individuals with type 2 diabetes as an effective tool in lowering glycated hemoglobin (Hb1Ac) and required doses of hypoglycemic drugs. The long-term studies indicate a possible beneficial effect of KD on cardiovascular function due to improvement lipid profile, changes in apolipoprotein (Apo) A1, adiponectin, and intercellular adhesion molecule-1 (ICAM-1).